INVESTIGATION OF PHOTOCATALYTIC EFFECT OF THIN FILMS FOR CONTAMINATED WATER TREATMENT - ISAHI, VICTOR (Kabarak University, 2023)
Removal of pollutants in water has been a challenge and poses significant risk to human health. As a result, research initiatives aimed to eliminate these pollutants have been on the rise. Photocatalysis has shown incredible potential for water treatment since it is affordable and utilizes solar energy. Tin (IV) Oxide ( ) has ardently been investigated as a photocatalyst for water treatment due to its remarkable properties, nontoxicity, and stability. However, its wide-bandgap and the tendency for some electrons and holes to recombine have been cited among the limiting factors. This study, therefore, aimed at preparing and optimizing Tin (IV) Oxide ( ) thin film by doping it with varied proportions of Tungsten (VI) Oxide ( ) and to investigate the effect of doping on the optical, structural and photocatalytic properties of the prepared samples. Pure and five groups of ( of 0.1, 0.3, 0.5, 1.5, and 2.0 wt.%) thin films were successfully fabricated through Sol-gel Spin coating technique at a rotary speed of 1200rpm for 30 seconds followed by annealing at 500 ºC for 1hr. The average thickness of the prepared films was 135.4 nm. The photocatalytic properties of the prepared samples were analyzed by studying the photo degradation of methylene blue dye under UV light. The calculated rate constants for undoped was 0.00256 min-1 while (1.5%wt.) yielded a degradation rate constant of 0.00519 min-1 which was twice that of pure films. The mechanism involved in the enhancement of the photocatalytic efficiency of the thin film due to the addition of is explained based on optical and structural characterization. Doping improved the optical absorbance of the films and caused a red shift on the absorption edge of the films, decreasing the band gap from 3.82 to 3.03 eV. X-ray Diffraction (XRD) studies revealed that the prepared samples were, polycrystalline in structure, with the crystallite size of pure increasing after being doped by . These results show that low-cost photocatalyst is a good candidate to eliminate organic pollutants from contaminated water, which cause severe threats to health and the environment.
Keywords: Photocatalysis; Tin (IV) Oxide; Tungsten (VI) Oxide; Pollutants